2013
DOI: 10.1016/j.physletb.2013.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Onαcorrections inN=1F-theory compactifications

Abstract: We consider N = 1 F-theory and Type IIB orientifold compactifications and derive new α ′ corrections to the four-dimensional effective action. They originate from higher derivative corrections to eleven-dimensional supergravity and survive the M-theory to F-theory limit. We find a correction to the Kähler moduli depending on a non-trivial intersection curve of seven-branes. We also analyze a four-dimensional higher curvature correction.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 38 publications
6
86
0
Order By: Relevance
“…It therefore remains an open problem to show that these terms are absent in general. However, no such dangerous leading terms have been found in string theory so far, despite extensive attempts to understand them quantitatively, see for example []. It therefore may be that such leading terms are forbidden, or sufficiently suppressed, in string theory due to some as yet unknown reason, or simply that they have not been calculated due to the technical difficulty of the problem.…”
Section: Swampland Tests In String Theorymentioning
confidence: 99%
“…It therefore remains an open problem to show that these terms are absent in general. However, no such dangerous leading terms have been found in string theory so far, despite extensive attempts to understand them quantitatively, see for example []. It therefore may be that such leading terms are forbidden, or sufficiently suppressed, in string theory due to some as yet unknown reason, or simply that they have not been calculated due to the technical difficulty of the problem.…”
Section: Swampland Tests In String Theorymentioning
confidence: 99%
“…Ref. [] showed that N=1 O(α2) corrections to the effective action give rise to moduli redefinitions, while ref. [] found that N=1 O(α3) effects produce a shift of the CY Euler number term.…”
Section: De Sitter In String Theorymentioning
confidence: 99%
“…25 Because of the 'extended no-scale structure' [74,75], these corrections are negligible since they scale as V −10/3 whereas V α ′ behaves as V −3 . The last contribution V soft reads: 18) where the soft scalar mass for the matter field φ living in the bulk scales as the gravitino mass m 3/2 = e K/2 |W | ≃ |W 0 |/V suppressed by a factor of order ln(M P /m 3/2 ) [76,77] (c is 25 For recent activity on stringy perturbative corrections see [69][70][71][72][73].…”
Section: Jhep05(2014)001mentioning
confidence: 99%